PENGARUH KERJASAMA TIM, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PTPN VII (PERSERO) PADANG PELAWI - Fernando, Eric; Sismanto, Adi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
Research at PTPN VII (Persero) Padang Pelawi with the formulation of the problem How is the influence of Teamwork, Compensation, Work Discipline on Employee Performance at PTPN VII (Persero) Padang Pelawi and The purpose of this research is to find out Teamwork, Compensation, Work Discipline on Employee Performance at PTPN VII (Persero) Padang Pelawi The population used in this study were all employees of PTPN VII (Persero) Padang Pelawi totaling 110 respondents. The sampling technique used total sampling based on predetermined criteria totaling 110 respondents. Observation data collection techniques, documentation and questionnaires. The data that has been processed is analyzed using the SPSS 24 formula. Based on research and calculations using the SPSS 26.00 program from the table it is found that: From the variables Teamwork (X1), Compensation (X2), and Work Discipline (X3) the most dominant influence on Employee Performance (Y) at PTPN Nusantara VII Seluma Regency, namely the results of research conducted are Teamwork and Compensation factors that have a relationship a significant value of 0.000. This indicates that from the variables Teamwork (X1), Compensation (X2), and Work Discipline (X3) which affect Employee Performance (Y), PTPN VII (Persero) Padang Pelawi Seluma Regency has a very significant relationship. Keywords: Teamwork, Compensation, Work Discipline, Employee Performance